Political transhumanism – future without crisis? - Misztal, Dawid (Hybris, 2018)
As is the case with every utopian vision of the future, transhumanism offers some social and political solutions. In recent years transhumanists on both sides of the Atlantic have been trying to make this ideas visible and hearable in the political mainstream, which makes them all the more interesting. The text examines the set of beliefs supported and promoted by political transhumanism in order to estimate their persuasiveness and their potential efficiency in dealing with the problems they allegedly would solve. First I try to present the general profile of the political dimension of transhumanism. Then, as a result, two main transhumanist political stances are distinguished: technolibertarianism and technoprogressivism. This allows to analyse the functioning of the notion of crisis in the political rhetoric of transhumanism.